Targeting insect mitochondrial complex I for plant protection - Wu, Xiu‐Ming (Plant Biotechnol J, 2016)
Plant engineered to express double‐stranded RNA (dsRNA) can target the herbivorous insect gene for silencing. Although mounting evidence has emerged to support feasibility of this new pest control technology, field application is slow largely due to lack of potent targets. Here, we show that suppression of the gene encoding NDUFV2, a subunit of mitochondrial complex I that catalyses NADH dehydrogenation in respiratory chain, was highly lethal to insects. Feeding cotton bollworm (Helicoverpa armigera) larvae with transgenic cotton tissues expressing NDUFV2 dsRNA led to mortality up to 80% within 5 days, and almost no larvae survived after 7 days of feeding, due to the altered mitochondrial structure and activity. Transcriptome comparisons showed a drastic repression of dopa decarboxylase genes. Reciprocal assays with Asian corn borer (Ostrinia furnacalis), another lepidopteran species, revealed the sequence‐specific effect of NDUFV2 suppression. Furthermore, the hemipteran lugus Apolygus lucorum was also liable to NDUFV2 repression. These data demonstrate that the mitochondrial complex I is a promising target with both sequence specificity and wide applicability for the development of new‐generation insect‐proof crops.